A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 3 (Revision of the azureipennis, cupricollis, iridicolor and melanura species groups) - Levey, Brian (Zootaxa, 2023)
This is the third part of a revision of the Australian members of the genus Melobasis Laporte & Gory 1837 and revises the species of the azureipennis, cupricollis, iridicolor and melanura species groups. 19 new species are described: M. adamsi sp. n., M. adusta sp. n., M. aureoviridis sp. n., M. aureovittata sp. n., M. breviantennatus sp. n., M. calama sp. n., M. confundo sp. n., M. cuspidata sp. n., M. dentata sp. n., M. edungalbensis sp. n., M. fritzbrechteli sp. n., M. imitator sp. n., M. incisa sp. n., M. incongruens sp. n., M. macqueeni sp. n., M. oculata sp. n., M. ordinata sp. n., M. rufoviolacea sp. n., M. tricolor sp. n. The following new synonymies are proposed: M. abigailae Turner & Hawkeswood, 2009 is synonymised with M. cupricollis Kerremans, 1898; M. epistomalis Obenberger, 1942 is synonymised with M. costata Macleay, 1872; M. macleayana Obenberger, 1930 is synonymised with M. suturalis Thomson, 1879; M. viridiobscura Thomson, 1879 is synonymised with M. suturalis Thomson, 1879.The following changes of status are proposed: M. azureipennis Macleay, 1872 and M. aureipennis Thomson, 1879 are removed from synonymy with M. cyaneipennis Boheman, 1858, which is transferred to the genus Nesotrinchus Obenberger; M. suturalis Thomson, 1879 is removed from synonymy with M. apicalis Macleay, 1872; M. viridiobscura Thomson, 1879 is removed from synonymy with M. obscurella Thomson, 1879.